Metatranscriptomic virome assessment of Rhipicephalus microplus from Colombia (2020)
Ticks (Ixodida) are hematophagous ectoparasites that harbor and transmit diverse species of viruses, some of which cause serious diseases with worldwide veterinary and human health consequences. Rhipicephalus microplus is an important cattle tick in Colombia, where it causes significant economic losses. Despite the importance of this tick, its viral profile is unknown. RNA sequencing was used in this study as a surveillance method for virus detection in R. microplus. Most of the viral origin contigs were assigned to two putative viruses: one chuvirus (Wuhan tick virus 2) and one phlebovirus-like (Lihan tick virus). In addition, viral contigs corresponding to two jingmenviruses previously reported in R. microplus from China and Brazil were detected, as well as a novel putative tymovirus, named here as Antioquia tymovirus-like 1 (ATV-like 1). The presence of some of these viruses across numerous regions in the world could have several explanations, including i) a long-term association between those viruses and R. microplus and ii) a consequence of livestock historical trade. Our results shed new light on the virus diversity of this tick species and provide a basis for further studies on the evolutionary history and pathogenic potential of these interesting viruses.